A kind of ECTFE melt-blown filter material and preparation method thereof

By mixing ECTFE resins with different melt indexes and optimizing meltblown nonwoven processes, the processing problems of ECTFE materials in the prior art were solved, and high-performance ECTFE meltblown filter materials were prepared, suitable for high-temperature and corrosion-resistant environments, and high filtration was achieved Combination of precision and mechanical strength.

CN114618233BActive Publication Date: 2025-01-10ZHEJIANG RES INST OF CHEM IND CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202011470953.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-14
Publication Date
2025-01-10
Estimated Expiration
2040-12-14

AI Technical Summary

Technical Problem

The difficulty in efficiently processing and application of ECTFE materials with high melt index has resulted in limited application in the filtration field and the lack of suitable solvents has led to processing difficulties.

Method used

By selecting ECTFE resins with different melt indexes for mixing, the mechanical properties and filtration accuracy of the material are adjusted, and meltblown nonwoven technology is used to prepare ECTFE meltblown filter materials with high pore size and fiber diameter, combining antioxidants and Hastelloys Equipment, optimize screw design and blowing conditions, improve the tensile strength and filtration performance of the material.

Benefits of technology

It realizes high filtration accuracy, mechanical strength and a wide range of application ECTFE meltblown filter materials, suitable for high temperature, acid and alkali and corrosion environments, and improves production efficiency and material quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0002833901610000011
    Figure HDA0002833901610000011
  • Figure HDA0002833901610000012
    Figure HDA0002833901610000012
  • Figure HDA0002833901610000021
    Figure HDA0002833901610000021
Patent Text Reader

Abstract

The invention discloses an ECTFE melt-blown filter material and a preparation method thereof, wherein the ECTFE melt-blown filter material has an average pore size of 0.1 μm to 100 μm, a fiber diameter of 0.05 μm to 50 μm, a longitudinal tensile breaking strength of 15 N to 100 N, and a transverse tensile breaking strength of 10 N to 50 N. The ECTFE melt-blown filter material of the invention has high tensile strength, high elongation at break, high filtering accuracy, and is suitable for harsh environments such as high temperature resistance, acid and alkali resistance, and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and in particular relates to an ECTFE melt-blown filter material. Background Art

[0002] Meltblown nonwoven technology is an important means of efficiently producing and processing industrial textiles. Its products have the characteristics of short process flow, high production efficiency, ultrafine fibers, large specific surface area, and high porosity. It has unique advantages in the fields of medical protection, high-efficiency filtration, thermal insulation, sound absorption and noise reduction, and battery separators. The early application of meltblown nonwovens was mainly filter materials, suitable as filter materials for gas-solid separation or liquid-solid separation. The mesh pores of meltblown nonwoven filter materials enhance the dispersion effect and can improve the filtration effect. It has an ultrafine fiber structure with small and numerous micropores, which has a strong interception and screening effect on particulate matter. At present, the meltblown nonwoven products in the domestic market are mainly polypropylene (PP). Other polymer meltblown nonwoven products include polyester (PET), polyamide (PA), polyethylene (PE), polyurethane (PU), polylactic acid (PLA), polyphenylene sulfide (PPS) and ethylene-trifluorochloroethylene copolymer (ECTFE), which are still in the research and development stage.

[0003] ECTFE is a copolymer of ethylene and chlorotrifluoroethylene in a 1:1 ratio. It is a semi-crystalline, thermoplastic polymer with a brittle temperature below -76°C and a melting point between 220 and 260°C. It can be used for a long time at temperatures above 150°C. ECTFE has excellent solvent resistance, including common corrosive chemicals and organic solvents. It is particularly suitable for high-temperature and highly corrosive separation environments. It has broad application prospects in the separation field and is a potential ideal filter material.

[0004] Since there is no solvent suitable for ECTFE at room temperature, ECTFE is generally processed by hot melt method. Meltblown nonwoven technology is the main processing method of ECTFE after thermally induced phase separation. Meltblown nonwoven technology is one of the direct polymer web forming methods. It is to form ultrafine fibers by extremely stretching the polymer melt extruded by the screw extruder through high-speed high-temperature airflow blowing or other means, and then gather them on the web forming roller or the web forming curtain to form a fiber web, and finally reinforce them by self-adhesion to form a meltblown nonwoven fabric. U.S. Patent US5470663A proposes that vinyl fluoropolymers can be processed by meltblowing technology. The ECTFE melt index used in this patent is lower than 1500g / 10min (190℃, 2.16kg), and it is impossible to process raw materials with higher melt index. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes an ECTFE melt-blown filter material with high filtering accuracy, high mechanical strength and wide application range.

[0006] The objective of the present invention is achieved through the following technical solutions:

[0007] A ECTFE melt-blown filter material has an average pore size of 0.1 μm to 100 μm, a fiber diameter of 0.05 μm to 50 μm, a longitudinal tensile breaking strength of 15 N to 100 N, and a transverse tensile breaking strength of 10 N to 50 N.

[0008] Preferably, the average pore size of the melt-blown filter material is 0.1μm to 50μm, the fiber diameter is 0.05μm to 30μm, the longitudinal tensile breaking strength is 15N to 50N, and the transverse tensile breaking strength is 10N to 30N; more preferably, the average pore size of the melt-blown filter material is 0.1μm to 10μm, the fiber diameter is 0.05μm to 20μm, the longitudinal tensile breaking strength is 15N to 30N, and the transverse tensile breaking strength is 10N to 15N.

[0009] The ECTFE melt-blown filter material is prepared from one ECTFE resin or a mixture of two or more ECTFE resins with different melting indexes, and the melting index of the ECTFE resin is 300g / 10min to 2000g / 10min (2.16kg, 230°C).

[0010] The present invention adjusts the corresponding performance of the ECTFE melt-blown filter material by selecting ECTFE resins with different melt indexes as raw materials. The larger the melt index of the ECTFE resin, the smaller its melt viscosity, the better the melt fluidity, the easier it is to be blown by the drafting wind force, and the finer the fiber pore size of the prepared ECTFE melt-blown filter material. However, if the melt index of the ECTFE resin is too large, the mechanical properties such as tensile breaking strength of the prepared ECTFE melt-blown filter material will be reduced.

[0011] Preferably, the ECTFE melt-blown filter material is prepared from a mixture of two or more ECTFE resins with different melt indexes. The ECTFE resin mixture with different melt indexes is heated and plasticized by a twin-screw to form a melt, and a gradient distribution is formed in the screw, and the fluidity is enhanced, thereby obtaining ultrafine fibers with good mechanical properties.

[0012] Specifically, the ECTFE resin mixture with different melt indexes includes ECTFE resin A and ECTFE resin B. The melt index of the ECTFE resin A is 800g / 10min-1200g / 10min (2.16kg, 230°C); the melt index of the ECTFE resin B is 300g / 10min-2000g / 10min (2.16kg, 230°C), which can be specifically selected according to different application scenarios and filtering requirements. When the ECTFE melt-blown filter material needs to have a higher tensile breaking strength, the melt index of the ECTFE resin B is 300g / 10min-800g / 10min (2.16kg, 230°C); when the ECTFE melt-blown filter material needs to have a higher filtering accuracy, the melt index of the ECTFE resin B is 1200g / 10min-2000g / 10min (2.16kg, 230°C).

[0013] The present invention also provides a method for preparing any of the above-mentioned ECTFE melt-blown filter materials, which has a short process flow and high production efficiency, and the specific steps are as follows:

[0014] S1, heating ECTFE resin and antioxidant into ECTFE melt in an extruder at a heating temperature of 180°C to 280°C;

[0015] S2. ECTFE melt forms ultrafine fibers under the blowing of high-speed and high-temperature airflow, and forms a fiber web on a mesh roller or a mesh curtain;

[0016] S3. The fiber web is made into ECTFE melt-blown filter material through self-bonding or hot pressing.

[0017] Specifically, the present invention mixes ECTFE resin and antioxidant uniformly in a kneader or mixer, then adds the mixture into a twin-screw extruder, heats and melts the mixture to obtain a homogeneous ECTFE melt, passes through a spinneret, and forms ultrafine fibers under the blowing of high-speed and high-temperature airflow.

[0018] Preferably, the ECTFE resin is in the form of powder or pellets.

[0019] The discoloration of fluorinated polymers is basically caused by discoloration groups, such as conjugated unsaturated bonds. With the generation of conjugated unsaturated bonds, hydrogen halide gas will be generated. HF gas will be generated in the reaction system of the present invention, and the processing equipment used is preferably made of Hastelloy to prevent corrosion. Therefore, the screw and barrel of the twin-screw extruder are made of Hastelloy.

[0020] The aspect ratio of the extruder screw is an important parameter of the screw. When other conditions are constant, increasing the aspect ratio is equivalent to increasing the length of the screw, thereby increasing the time that the ECTFE resin stays in the screw, ensuring that the ECTFE resin has sufficient time to melt, which is beneficial to improving the quality of the ECTFE melt-blown filter material. Increasing the length can also reduce pressure flow and leakage flow, thereby improving the production capacity of the extruder. However, an excessively large aspect ratio can easily cause the ECTFE resin to stay in the screw for too long and produce thermal decomposition. Therefore, the selection of the aspect ratio should be determined based on the processing performance, product quality and productivity of the ECTFE resin. The aspect ratio of the screw described in the present invention is 15:1 to 60:1, preferably 35:1 to 40:1.

[0021] The function of the antioxidant is to delay and inhibit the oxidation process of the polymer, mainly by inhibiting the generation of free radicals and the decomposition of hydroperoxides to prevent the yellowing of the polymer. Preferably, the antioxidant is selected from tris (2,4-di-tert-butylphenyl) phosphite, bis (2,4-di-tert-butylphenyl) propionate] pentaerythritol diphosphite, dioctadecyl pentaerythritol diphosphite, 5,7-di-tert-butyl-3-(3,4-dimethylphenyl)-3H-benzofuran-2-one, dimethylbenzene dibutylbenzofuranone, 1,3,5-tris (3,5-di-tert-butyl 4-hydroxybenzyl)-s-triazine-2,4,6-( At least one of 1H, 3H, 5H) trione, 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxo-3,9-diphosphobicyclo[5.5]undecane, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, distearyl thiodipropionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, zinc stearate, calcium stearate, and rare earth zinc stearate.

[0022] Preferably, the antioxidant content is 0.0008-0.02.

[0023] According to the above-mentioned method for preparing ECTFE melt-blown filter material, preferably, the temperature of the high-speed high-temperature airflow is 200°C to 300°C, and the wind pressure is 0.015MPa to 0.1MPa; the temperature of the mesh roller or mesh curtain is 5°C to 40°C.

[0024] According to the above-mentioned method for preparing ECTFE melt-blown filter material, preferably, the distance between the mesh roller or mesh curtain and the die lip for blowing ultrafine fibers is 5 cm to 50 cm. Further preferably, the distance between the mesh roller or mesh curtain and the die lip for blowing ultrafine fibers is 0 cm to 30 cm.

[0025] Under the condition of constant hot air flow rate, the greater the distance between the mesh roller and the die lip, the longer the time for the meltblown filament to reach the mesh roller from the die lip, and the more obvious the temperature drop. After the temperature of the meltblown filament is reduced, it is not easy to be stretched by the hot air and become thinner, so the distance between the mesh roller and the die lip will seriously affect the diameter of the meltblown filament, that is, the greater the distance between the mesh roller and the die lip, the thicker the diameter of the meltblown filament.

[0026] According to the above-mentioned method for preparing ECTFE melt-blown filter material, preferably, in step S3, the hot pressing temperature is 100° C. to 200° C., the hot pressing pressure is 0.01 MPa to 5 MPa, and the hot pressing time is 0 to 10 s.

[0027] The present invention also provides the use of any of the above-mentioned ECTFE melt-blown filter materials, which can be used as a filter membrane in a filter assembly and applied to TFT-LCD etching and cleaning. Preferably, the other components of the filter assembly include a core column, a support mesh, a shell and an end cap, etc., which are all processed from ECTFE melt-blown filter materials with a melt index of 5g / 10min to 25g / 10min (230°C, 21.6kg).

[0028] Compared with the prior art, the present invention has the following beneficial effects: the ECTFE melt-blown filter material of the present invention has high tensile strength, high elongation at break, high filtration accuracy, and is suitable for harsh environments such as high temperature resistance, acid and alkali resistance, and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is a schematic diagram of the melt-blowing process of the present invention;

[0030] Figure 2 This is the front structure of the meltblown filter material in Example 1 of the present invention;

[0031] Figure 3 This is an enlarged view of the front structure of the meltblown filter material in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0033] Example 1

[0034] Weigh 600g of ECTFE resin with a melt index of 600g / 10min (230℃, 2.16kg) and 6g of ECTFE resin with a melt index of 1200g / 10min (230℃, 2.16kg), and use a kneader to mix evenly to obtain a solid mixed material. Then, the solid material is added to the extruder by manual feeding, and the extruder screw is completely melted and extruded at 210℃, and high-speed high-temperature airflow is used to blow to obtain ECTFE ultrafine fibers collected on the roller. During hot rolling, the temperature is 100℃, the pressure is 0.05MPa, and the time is 10s. The longitudinal tensile breaking strength of the prepared melt-blown filter material is 17N, the transverse tensile breaking strength is 12N, the fiber diameter is 0.08μm, and the average pore size is 0.5μm.

[0035] Example 2

[0036] Weigh 600g of ECTFE resin with a melt index of 600g / 10min (230℃, 2.16kg) and 6g of tri(2,4-di-tert-butylphenyl)phosphite, and use a kneader to mix them evenly to obtain a solid mixed material. Then, the solid material is added to the extruder by manual feeding, and the extruder screw is completely melted and extruded at 210℃, and high-speed high-temperature airflow is used to blow to obtain ECTFE ultrafine fibers collected on rollers. During hot rolling, the temperature is 100℃, the pressure is 0.05MPa, and the time is 10s. The prepared melt-blown filter material has a longitudinal tensile breaking strength of 20N, a transverse tensile breaking strength of 13N, a fiber diameter of 0.3μm, and an average pore size of 0.8μm.

[0037] The tensile breaking strength is higher than that of Example 1. This is because as the polymer melt index decreases, the spherulite size of the prepared melt-blown membrane filter material becomes larger, and the tensile breaking strength becomes larger.

[0038] Comparative Example 1

[0039] The operation of Comparative Example 1 is the same as that of Example 1, except that 600 g of ECTFE resin with a melt index of 600 g / 10 min (230° C., 2.16 kg) and 600 g of ECTFE resin with a melt index of 2500 g / 10 min (230° C., 2.16 kg) are used as raw materials.

[0040] The prepared melt-blown membrane filter material has a longitudinal tensile breaking strength of 8N, a transverse tensile breaking strength of 6N, a fiber fineness of 0.06 μm, and an average pore size of 0.3 μm.

[0041] Comparative Example 2

[0042] The operation of Comparative Example 2 is the same as that of Example 1, except that the antioxidant tris(2,4-di-tert-butylphenyl)phosphite is not added.

[0043] It can be seen from Comparative Example 2 that as the ECTFE resin is in the extruder for a longer time, black spots appear on the surface of the ultrafine fibers.

[0044] Comparative Example 3

[0045] The operation of Comparative Example 3 is the same as that of Example 1, except that: a 316 material melt-blowing device is used to carry out the ECTFE resin melt-blowing experiment, which results in carbonization in the barrel and the spinneret.

[0046] Example 3

[0047] The ECTFE melt-blown filter material obtained in Example 1 was immersed in 5% HCl aqueous solution, 5% NaOH aqueous solution, and 1% NaOH and 1% NaClO mixed aqueous solution for 72 hours, respectively. The color, appearance and mechanical properties of the filter material did not change significantly.

[0048] Comparative Example 4

[0049] The operation of Comparative Example 4 is the same as that of Example 1, except that PVDF resin is used as the raw material to prepare the filter material.

[0050] The prepared filter material was then immersed in a 5% HCl aqueous solution, a 5% NaOH aqueous solution, and a mixed aqueous solution of 1% NaOH and 1% NaClO for 72 hours. The color of the filter material turned black and the mechanical properties decreased by more than 50%.

Claims

1. An ECTFE melt-blown filter material, characterized in that: The melt-blown filter material has an average pore size of 0.1 μm to 0.5 μm, a fiber diameter of 0.05 μm to 0.3 μm, a longitudinal tensile breaking strength of 15 N to 100 N, and a transverse tensile breaking strength of 10 N to 50 N. The ECTFE melt-blown filter material is prepared from a mixture of two or more ECTFE resins with different melt indexes, wherein the mixture of ECTFE resins with different melt indexes comprises ECTFE resin A and ECTFE resin B, wherein the melt index of ECTFE resin A at 230°C and 2.16kg is 800g / 10min to 1200g / 10min; and the melt index of ECTFE resin B at 230°C and 2.16kg is 1200g / 10min to 2000g / 10min.

2. The ECTFE melt-blown filter material according to claim 1, characterized in that: The longitudinal tensile breaking strength of the melt-blown filter material is 15N to 50N, and the transverse tensile breaking strength is 10N to 30N.

3. The ECTFE melt-blown filter material according to claim 1, characterized in that: The longitudinal tensile breaking strength of the melt-blown filter material is 15N to 30N, and the transverse tensile breaking strength is 10N to 15N.

4. The method for preparing the ECTFE melt-blown filter material according to any one of claims 1 to 3, characterized in that: The steps of the preparation method are as follows: S1, heating ECTFE resin and antioxidant in an extruder to form ECTFE melt, the heating temperature is 180°C to 280°C; S2, the ECTFE melt is blown into ultrafine fibers by a high-speed and high-temperature airflow, and a fiber web is formed on a mesh roller or a mesh curtain; S3, the fiber web is made into ECTFE melt-blown filter material by self-bonding or hot pressing.

5. The method for preparing the ECTFE melt-blown filter material according to claim 4, characterized in that: In step S1, the extruder is a twin-screw extruder, the screw and barrel of the twin-screw extruder are made of Hastelloy, and the aspect ratio of the screw is 15:1 to 60:

1.

6. The method for preparing the ECTFE melt-blown filter material according to claim 4, characterized in that: The antioxidant is selected from tris(2,4-di-tert-butylphenyl)phosphite, bis(2,4-di-tert-butylphenyl) propionate pentaerythritol diphosphite, dioctadecyl pentaerythritol diphosphite, 5,7-di-tert-butyl-3-(3,4-dimethylphenyl)-3H-benzofuran-2-one, dimethylbenzene dibutylbenzofuranone, 1,3,5-tris(3,5-di-tert-butyl 4-hydroxybenzyl)-s-triazine-2,4,6-(1H, At least one of 3H, 5H) trione, 3,9-bis(2,4-di-tert-butylphenoxy)-2,4,8,10-tetraoxo-3,9-diphosphobicyclo[5.5]undecane, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, distearyl thiodipropionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, zinc stearate, calcium stearate, and rare earth zinc stearate.

7. The method for preparing the ECTFE melt-blown filter material according to claim 4, characterized in that: In step S2, the temperature of the high-speed high-temperature airflow is 200°C to 300°C, and the wind pressure is 0.015MPa to 0.1MPa; the temperature of the mesh roller or the mesh curtain is 5°C to 40°C.

8. The method for preparing the ECTFE melt-blown filter material according to claim 4, characterized in that: In step S3, the hot pressing temperature is 100°C to 200°C, the hot pressing pressure is 0.01MPa to 5MPa, and the hot pressing time is 0 to 10s.

9. The use of the ECTFE melt-blown filter material according to any one of claims 1 to 3, characterized in that: The melt-blown filter material is used as a filter membrane in a filter assembly and is applied to TFT-LCD etching and cleaning.

Citation Information

Patent Citations

  • Meltblowing of ethylene and fluorinated ethylene copolymers

    US5470663A

  • Ultrafine melt-blown non-woven fabric mixed material, melt-blown non-woven fabric prepared from same, and manufacturing method thereof

    CN101665993A

  • Preparation method of solvent-resistant polyethylene-chlorotrifluoroethylene separation membrane

    CN109758927A

  • Production of filter, filter cartridge and nonwoven fabric for filter

    JP1996318115A